In vitro activity of bacteriophages against planktonic and biofilm populations assessed by flow cytometry - Pires, Diana Priscila Penso (2018)
The in vitro activity of bacteriophages against planktonic cultures and biofilms is commonly evaluated by culture methods. However, these methods can lead to an underestimation of total bacterial cells when they undergo different physiological states. This chapter describes the methodology used to assess the in vitro activity of bacteriophages against planktonic cultures of bacteria in different metabolic states and biofilm populations by flow cytometry.